Increasing oat β-glucan viscosity in a breakfast meal slows gastric emptying and reduces glycemic and insulinemic responses but has no effect on appetite, food intake, or plasma ghrelin and PYY responses in healthy humans: a randomized, placebo-controlled, crossover trial. Issue 2 (12th December 2019) - Wolever, Thomas M S; Tosh, Susan M; Spruill, Susan E; Jenkins, Alexandra L; Ezatagha, Adish; Duss, Ruedi; Johnson, Jodee; Chu, YiFang; Steinert, Robert E
ABSTRACT: Background: The viscosity of oat β-glucan (OBG) determines its effect on serum cholesterol and glycemic responses, but whether OBG viscosity affects gastric emptying, appetite, and ad libitum food intake is unknown. Objectives: We aimed to determine the effect of altering the amount or molecular weight (MW) and, hence, viscosity of OBG in a breakfast meal on the primary endpoint of food intake at a subsequent meal. Methods: Overnight-fasted males ( n  = 16) and nonpregnant females ( n  = 12) without diabetes, aged 18–60 y, with BMI 20.0–30.0 kg/m² who were unrestrained eaters participated in a double-blind, randomized, crossover study at a contract research organization. Participants consumed, in random order, breakfast meals equivalent in weight, energy, and macronutrients consisting of white-bread, butter, jam, and 2% milk plus hot cereal [Cream of Rice (CR), or instant-oatmeal plus either 3 g oat-bran (2gOBG), 10 g oat-bran (4gOBG), or 10 g oat-bran plus β-glucanase (4gloMW) to reduce OBG MW and viscosity compared with 4gOBG]. Gastric emptying, subjective appetite, and glucose, insulin, ghrelin, and peptide tyrosine tyrosine (PYY) responses were assessed for 3 h and then subjects were offered an ad libitum lunch (water and pizza). Results: Pizza intakes ( n  = 28) after CR, 2gOBG, 4gOBG, and 4gloMW (mean ± SEM: 887 ± 64, 831 ± 61, 834 ± 78, and 847 ± 68 kcal, respectively) were similar (nonsignificant). Compared with CR, 4gOBG significantly reduced glucose (78 ± 10 compared with 135 ± 15 mmol × min/L) and insulin (14.0 ± 1.6 compared with 26.8 ± 3.5 nmol × min/L) incremental area-under-the-curve and delayed gastric-emptying half-time (geometric mean: 285; 95% CI: 184, 442, compared with geometric mean: 105; 95% CI: 95, 117 min), effects not seen after 4gloMW. Subjective appetite, PYY, and ghrelin responses after 2gOBG, 4gOBG, and 4gloMW were similar to those after CR. Conclusions: The results demonstrate that OBG viscosity determines its effect on postprandial glucose, insulin, and gastric emptying. However, we were unable to demonstrate a significant effect of OBG on appetite or food intake, regardless of its viscosity. This trial was registered at clinicaltrials.gov as NCT03490851.